The euro crisis and constitutional pluralism : financial stability but constitutional inequality - Tuominen, Tomi (Elgar studies in European law and policy, 2021)
"This insightful book assesses the theory of constitutional pluralism in light of the events of the Eurozone crisis of the past decade. Based on an analysis of how national courts reviewed the crisis response mechanisms and participated in the European-level political process, Tomi Tuominen argues that constitutional pluralism is not a valid normative theory of European constitutionalism. The analysis of crisis response mechanisms focuses on how the lack of a proper economic policy competence for the EU affected the formation of the measures and is at the root of the criticism concerning these mechanisms. Furthermore, the author connects discussions on the Eurozone crisis and constitutional pluralism in an innovative fashion, whilst also explaining how asymmetry and pluralism are linked. A novel reading on the horizontal and vertical aspects of Article 4(2) TEU is also developed throughout. Utilizing up-to-date and original analyses, The Euro-Crisis and Constitutional Pluralism will be an important read for scholars and students of European law, EU constitutional law and public policy"--